Longer nilpotent series for classical unipotent groups - Maglione, Josh, author; Wilson, James, advisor; Hulpke, Alexander, committee member; Boucher, Christina, committee member (Colorado State University. Libraries, 2013)
We compute the adjoint series for the unipotent subgroup, U, of the Chevalley group Ad(Zp). The adjoint series of U has length d2/4 + d/2 + θ(1), whose factors have order equal to either p or p2, whereas the lower central series of U has length d + 1, whose factors have order equal to pO(d). We provide an algorithm for computing the adjoint series.